2017
DOI: 10.1111/1346-8138.14017
|View full text |Cite
|
Sign up to set email alerts
|

Successful TS‐1 monotherapy as the second‐line treatment for advanced extramammary Paget's disease: A report of two cases

Abstract: There is no standard chemotherapeutic treatment for advanced extramammary Paget's disease, though the effectiveness of some chemotherapy regimens, including docetaxel, has been reported. In this report, we report that TS-1 monotherapy was effective in two patients with advanced extramammary Paget's disease after docetaxel treatment failure. TS-1 monotherapy may be useful as the second-line treatment for patients with advanced extramammary Paget's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Kato et al . recently reported favorable response in two patients with TS‐1 monotherapy following docetaxel resistance . As nearly 60% of EMPD demonstrates HER2 gene amplification, trastuzumab and paclitaxel have yielded favorable responses in many individual reports .…”
Section: Nonsurgical Interventionsmentioning
confidence: 99%
“…Kato et al . recently reported favorable response in two patients with TS‐1 monotherapy following docetaxel resistance . As nearly 60% of EMPD demonstrates HER2 gene amplification, trastuzumab and paclitaxel have yielded favorable responses in many individual reports .…”
Section: Nonsurgical Interventionsmentioning
confidence: 99%
“…Although several therapeutic modalities such as radiation therapy, chemotherapy, and molecular targeted therapy have been reported, their efficacy in treating unresectable EMPD is unsatisfactory. Thus, new treatment modalities are required [4,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy of TS-1 monotherapy has also been reported in small number of cases [135]. Kato et al reported two cases of advanced EMPD in which TS-1 monotherapy was effective as a second line after docetaxel treatment failure [136]. It has been reported that TS-1 plus docetaxel exhibit synergistic antitumor effects because docetaxel reduces 5-FU metabolites, resulting in increased 5-FU [137].…”
Section: Chemotherapiesmentioning
confidence: 98%